Agama Dan Inovasi Kurikulum Pendidikan Aceh - Ichsan Thaib, Muhammad (Al Mabhats : Jurnal Penelitian Sosial Agama, 2018)
Aceh is an Indonesian province that has been granted autonomy rights to implement Islamic shari'ah in various dimensions of life, even though it is not yet full as it is still under the auspices of the state that adheres to the national system. It also covers education sector. Having the rights, Aceh has the authority to design curriculum in accordance with the contextual factors, such as the majority Muslim population. The curriculum is expected to have an impact on the curriculum it self. The curriculum is only a tool or instrument to achieve the educational and learning objectives set. The curriculum is not an end goal. Every activity to be carried out by a person or group of people, it must have a strong foundation as a basis so that what is carried out will actually produce innovation, including in designing an educational curriculum. Innovation can be produced in all fields including education. Innovation can be done anywhere and anytime. Especially in the field of education, innovation usually arises from the concerns and desires of certain parties about the implementation of education. Religion is the source of knowledge, where science is included in religion, discussed, given orientation, laid down principles and others. Science describes religious guidance, while religion provides the basis and strives to advance science that is analytical and practical. Then the religion of Islam provides value, nature, and a comprehensive view of life based on revelation. Like wise, with this spiritual or religious basis, the existing curriculum is expected to help students to have strong faith, be stead fast in religious teachings, be noble and strong with meaningful knowledge for living in the world and here after.